Coal dan Shale Carbonaceous Ngrayong Formation, Daerah Sale Area, Rembang Regency, Central Java Case Study : Study of Sedimentation terhadap Microscopic Characteristic of Pyritic Sulphur - Rahmad, Basuki; Sugeng Raharjo; Yody Rizkianto; Aris Buntoro; Dita Antari Setyaningsih; Obrin Trianda (ReTII, 2023)
This research discusses coal sedimentation and the microscopic characteristics of coal seam sulfur exposed in the Sale area, Rembang, Central Java. The regional geology of the Rembang area is in the Rembang-Madura Anticlinorium, including the back arc basin. The target formation in this research is the Ngrayong Formation. The research method used was sampling outcrops of coal and carbonaceous shale, then microscopically analyzing the macerals and minerals based on incisions from polished briquette blocks. The rock outcrops found in the study area consist of coal, channel sandstone and carbonaceous shale. The results of pollen analysis found index fossils of Florschuetzia Trilobata and Palmaepollenites Kutchensis relative ages of Middle Miocene Ngrayong Formation coal deposited in the Upper Delta Plain environment characterized by the presence of freshwater pollen taxa such as Cephalomappa, Stemonurus, Calophyllum type, Verrucatosporites Usmensis, Macaranga and Casuarina spp. Based on changes in the water column, the coal and carbonaceous shale sedimentation system of the Ngrayong formation occuring a change from high water characterized by high vitrinite content to low water characterized by less vitrinite content. Changes in sea tides in the transition area cause water sulphate ions to enter the swamp to form framboidal pyritic sulphur. Coal rank of coal Ngrayong Formation subbituminous (Rv 0,38-0,53)